Characteristics of 985 pediatric burn patients in the south of Liaoning province of China - Hongjun Zhai; Shuangrong Liu; Li Jiang; Bo Sun; Shijie Xin (Burns & Trauma, 2014)
Accidental injury due to burns is a serious and common, but preventable, occurrence in children. To analyze the characteristics of pediatric burns in the south of Liaoning province of China, a retrospective review was conducted of information, including general characteristics, demographics, etiology of burns, anatomical areas burned, and severity of injuries, obtained from medical records of pediatric burn patients admitted to the Burn Center of Anshan Hospital of the First Hospital of China Medical University from 2002 to 2011. Differences between age-groups and cause and severity of injuries were examined using Cochran-Mantel-Haenzsel (C-M-H) statistic or chi-square (χ2 ) analyses where appropriate. A total of 985 pediatric burn cases were included, with only one death. The maximal burn area recorded was 80% and the maximal third-degree burn area was 45%. The majority of burns (637/985, 64.67%) were moderate second-degree wounds, encompassing 5-14% of the total body surface area. The infant age-group (<3 years old) had the largest representation (622/985, 63.15%), with more males than females affected. Most of the injuries occurred at home in children living in the local region. Scalding accounted for 89.85% (885/985) of all injuries, with a decreasing incidence with age, whereas injuries due to flames and from electrical sources markedly increased with age. Only a minority of guardians (244/985, 24.77%) had burn prevention knowledge, and none of them knew how to provide first-aid treatment for burn injuries. These results indicate that the majority of pediatric burns occur in children less than 3 years of age from scalds received while at home. As a large proportion of these cases occurred in rural areas, programs emphasizing burn prevention and treatment knowledge should therefore be made more available to these families.